MULTILINGUAL LEGAL DISCOURSE AT THE COURT OF JUSTICE OF THE EUROPEAN UNION - Paluszek, Karolina (Comparative Legilinguistics, 2020)
The European Union is an organisation using multiple languages, and so does its law. Dealing with over twenty languages may be seen as an additional challenge in the interpretation of the provisions of the common legal order, so different from national legal systems of particular Member States. Multilingual interpretation has attracted a high interest of scholars all over the Europe (see Derlen 2009, Paunio, Doczekalska, Schubel-Pfister, Gemar, Sarcević, Pozzo, McAuliffe)[1]. Unlike most of other works, this article does not focus on the process of interpretation conducted by an adjudicating panel or an Advocate General but rather on the statements of the parties to a dispute or national courts requesting a preliminary ruling when referring to multilingualism. This work is divided into two separate parts. Firstly, the author focuses on the cases, where a national court or a party invokes the multilingual character of the EU-law. Several different ways of its application in the course of proceedings have been explained. The second part is dedicated to the issue of multilingualism of the EU case law. Unlike the EU law, the judgments of the Court of Justice, as well as the Advocate Generals’ opinions are authentic in certain languages only (accordingly – language of the Court proceedings and the language chosen by an Advocate General for a particular opinion). However, the research proved that the existing single authentic language version does not help in avoiding problems concerning multilingual character of the EU law and multilingual nature of the common European legal discourse. Both issues have been analysed based on the texts of judgments and opinions passed in recent cases solved by the CJEU. Of course, the statements of the parties or national courts referring to multilingualism do not always have a great influence on the final result of the case. Nevertheless, a unique perspective taken in this article can serve as a good illustration of various possibilities of making use of the linguistic comparison in the process of legal interpretation. [1] Currently, a research project providing complex and multidimensional analysis of the relationship of Law and Language in the context of EU law is being conducted by Karen McAuliffe and her team (is funding the “Law and Language at the European Court of Justice” Project http://www.llecj.karenmcauliffe.com).